Carbon nanotubes boosts the toughness and conductivity of wet-spun MXene fibers for fiber-shaped super capacitors. (5th November 2022) - Zhao, Xu; Zhang, Jizhen; Lv, Ke; Kong, Na; Shao, Yanqiu; Tao, Jinlong
Abstract: Mechanically strong and electrically conducting fibers, particularly those with high specific capacitances, are promising fiber-shaped electrodes for fiber- and textile-based energy storage devices like fiber-shaped supercapacitors (FSCs). However, a high loading of fillers or bridging agents is commonly required to fabricate fiber electrodes with good mechanical strength, which compromises electrical conductivity and energy storage performance. Herein, an easily scalable wet-spinning strategy is reported to fabricate multifunctional Ti3 C2 T x MXene/carbon nanotubes (MXene/CNT) hybrid fibers from a harmonious mixture of MXene and CNT in water and using acetic acid as a coagulation bath. The hybrid fiber achieved high strength (61 ± 7 MPa), good conductivity (1142.08 ± 40.04 S cm −1 ) and excellent energy storage performance (∼295 F g −1 at 5 mV s −1 ) at a very low CNT content of ∼1 wt%. When CNT loading increased to ∼9 wt%, the maximum strain at broken reached 161 ± 19 MPa and conductivity further increased to 1715 ± 22 S cm −1 . The excellent mechanical performance allows hybrid fibers to be knitted into textiles for energy storage textiles. The assembled FSCs exhibit energy and power densities of ∼6.08 mW h cm −3 and ∼6440 mW cm −3, respectively. The excellent performance of MXene/CNT fiber and good feasibility for scalable production will open up new opportunities for the development of wearable and textile-based devices in the near future. Graphical abstract: Image 1 Highlights: Large scale wet-spinning of MXene/CNT fibers with great fiber performance. CNTs infiltrated between MXene flakes and constructed good connection between MXene flakes. The excellent mechanical properties allow hybrid fibers to be weave into fabrics for energy storge applications.